Correction: Limited indirect effects of an infant pneumococcal vaccination program in an aging population. - Mark van der Linden; Matthias Imöhl; Stephanie Perniciaro (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0220453.].